Land Suitability Assessment for Sustainable Settlement in Serang Regency, Banten Province - Junaid, Muhammad; Anggara, Rifnaldi Bergas; Nagara, Rakyan Paksi; Wibowo, Adi (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Urbanization is the result of persistent population increase, which turns formerly agrarian areas into industrial and service-based hubs. This change prompts concerns about environmental degradation, including flooding, declining agricultural output, and air pollution, as well as a rise in demand for residential real estate, a limited resource. Goal 11 of the Sustainable Development Agenda, ”Building Inclusive, Safe, Resilient, and Sustainable Cities and Communities” addresses these problems. However, a comprehensive LSA incorporating local climate aspects has not been conducted for Serang Regency, an area with significant population growth and diverse land characteristics. This study aims to map the spatial distribution of suitable residential land in Serang Regency; evaluate the suitability of current residential areas; and assess the alignment of settlement plans with suitability criteria in the spatial plan. Findings reveal that 65.5% of Serang Regency is suitable for residential use, while 32% is unsuitable. Currently, 71.2% of settlements are in suitable areas, and 28.2% are in unsuitable ones. Future settlement plans show 90.7% alignment with suitable areas. These results indicate that, while spatial planning in Serang Regency has generally guided appropriate residential development, some areas still require attention for sustainability. This study provides valuable insights for policymakers aiming to foster sustainable, safe, and comfortable living environments.